Pembuatan Dan Karakterisasi Membran Selulosa Asetat Dari Serat Daun Nanas Untuk Pengolahan Limbah Pulp And Paper - Eka Putri Sriandriani; Jhon Armedi Pinem; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The membrane is a selective and semipermeable thin layer between two phases, namely the feed phase and permeate phase. One of the ingredients for making membranes is cellulose acetate from pineapple leaf waste. The purpose of this research is to make cellulose acetate membrane using cellulose from pineapple leaf waste as the main raw material with composition variation and pressure variations. In this research uses variations in polymer cellulose acetate are 15% (w/w), 20% (w/w) and 25% (w/w) and pressure variations are 1 bar, 2 bar and 3 bar. The stages of making membranes are taking pineapple leaf fibers, making cellulose acetate, making cellulose acetate membrane and testing the mechanical properties of the membrane. At optimum condition, flux value was obtained 22.26 L/m2.h at 3 bar with cellulose acetate composition 25% w/w. While the highest rejection value was obtained at a membrane composition of 25% w / w with COD 81.12%, BOD 76.03% and TSS 77.91% at 3 bar pressure. If more cellulose acetate composition were used, the flux value will be decrease and the rejection will be increase. If pressure increase, rejection and flux value will get higher. Keywords : cellulose acetate, flux, membrane, rejection.